Decellularized banana leaves: eco-friendly scaffolds for cell-based seafood - Banavar, Amiti; Sarkarat, Reyhaneh; Amirvaresi, Arian; Li, Xinxin; Nguyen, Cuong; Kaplan, David L.; Nitin, Nitin; Ovissipour, Reza (Frontiers in Sustainable Food Systems, 2024)
Cellular agriculture holds the potential to address sustainability, food security, and agricultural resilience. Within the cell-based meat supply chain, one of the key steps is developing sustainable scaffolding. In this study, we evaluated the impact of decellularized banana leaves, various coating materials including soy protein and gelatine, and different cell seeding strategies on cell viability, cell growth, cell alignment, and the response of the materials to thermal processing. Kinetics of the quality degradation of the scaffolds with and without cells were determined through kinetics equations. The efficiency of decellularization was verified through DNA quantification, which decreased from 445 ng/mg in fresh banana leaves to non-detectable levels in the decellularized samples. The alignment of cells on gelatin-coated samples was the highest among the samples, with a dominant orientation of 65.8°, compared to soy-coated and uncoated samples, with dominant orientations of 9.2° and −6.3°, respectively. The kinetics of shrinkage indicated that coating with soy and the presence of cells increased the activation energy due to the higher energy required for protein denaturation. The kinetics of area changes in plain scaffolds without cells followed a first-order pattern, while with seeded cells a second-order pattern was followed. Overall, the results showed that decellularized banana leaves provide sustainable scaffoldings for cellular agriculture applications. In addition, soy coating provided many benefits for decellularized samples by supporting cell adhesion and cell proliferation.